PENGARUH APLIKASI BIOINSEKTISIDA VITURA (S/NPV) DAN INSEKTISIDA SINTESIS DELTAMETRIN TERHADAP SERANGAN HAMA PADA TANAMAN BUNCIS (Phaseolus vulgaris L.) - Sudarmi Thalib (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2011)
PENGARUH APLIKASI BIOINSEKTISIDA VITURA (S/NPV) DAN INSEKTISIDA SINTESIS DELTAMETRIN TERHADAP SERANGAN HAMA PADA TANAMAN BUNCIS (Phaseolus vulgaris L.)The Application Effect of Vitura (S/NPV) Bioinsecticide and Synthetic Insecticide of Deltametrin on the Attack of Pests on Bean Crop (Phaseolus vulgaris L.)Sudarmi ThalibFakultas Pertanian Universitas MulawarmanSamarinda ABSTRACTPurposes of this research was to know the effect of Vitura (S/NPV) and Deltametrin on the attack intensity of pest and yield of bean. The experiment was conducted from March to June 2010 at Bukit Pinang Village, Samarinda. The research emploved the Randomized Completely Block Design (RCBD) wich consisted of six insecticide treatments, i.e. : Po = Control (ni Vitura and Deltametrin application), P1 = 0,75 g Vitura L -1 water, P2  = 1,5 g Vitura L-1 water, P3  = 5 g Deltametrin L-1 (no Vitura application), P4  = 0,75 g Vitura + 5 mg Deltametrin L-1 water and P5  =  1,5 g Vitura + 5 g Deltametrin L-1 water. All treatment were repeated 5 times. The result experiment showed that the treatment affected significantly to attack intensity of pest and yield of bean. The lowest intensity of pest attack and the highst bean yield was obtained on combination of Vitura and Deltametrin at concentration 1,5 g + 5 mg L-1 water.Key words : Bean, Pest, Vitura (S/NPV, Deltametrin.